Study on Creep Characteristics of Expansive Soil in High-Fill Channel of South-to-North Water Transfer Project. (12th November 2020) - Guo, Jianhua; Dai, Zhangjun; Li, Shichang; Muhammad, Nadeem; Gao, Hui
Abstract : In the Nanyang section of the midroute of the South-to-North Water Transfer Project, the expansive soil is often used as a filler for high-fill channels. After the channel is stabilized, the expansive soil undergoes creep deformation over time. Studying the creep characteristics of expansive soils in different environments is particularly important for evaluating the safe operation of high-fill channels. In the current study, the creep test of expansive soil under different moisture content and dry density was carried out. It is proposed that the slope of the fitted straight line in the compression curve of the expansive soil can be used to represent the secondary consolidation coefficient of unsaturated expansive soil, and the variation law of the secondary consolidation coefficient under different environmental factors is obtained. The modified Bjerrum calculation method considering the influence of additional load and lateral deformation yields the postexpansion soil settlement curve model to determine the control index range of the project site. Moreover, it is also observed that the secondary consolidation coefficient of unsaturated expansive soil increases with the increase of moisture content and decreases with the increase of dry density. The coefficient of secondary compression of unsaturated expansive soil is linearly related to dry density and moisture content. After the preconsolidation treatment of the expansive soil, when the load level is less than the preload, the secondary consolidation coefficient is smaller, otherwise the secondary consolidation coefficient is larger.